3x(x+3)=24

Simple and best practice solution for 3x(x+3)=24 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3x(x+3)=24 equation:


Simplifying
3x(x + 3) = 24

Reorder the terms:
3x(3 + x) = 24
(3 * 3x + x * 3x) = 24
(9x + 3x2) = 24

Solving
9x + 3x2 = 24

Solving for variable 'x'.

Reorder the terms:
-24 + 9x + 3x2 = 24 + -24

Combine like terms: 24 + -24 = 0
-24 + 9x + 3x2 = 0

Factor out the Greatest Common Factor (GCF), '3'.
3(-8 + 3x + x2) = 0

Ignore the factor 3.

Subproblem 1

Set the factor '(-8 + 3x + x2)' equal to zero and attempt to solve: Simplifying -8 + 3x + x2 = 0 Solving -8 + 3x + x2 = 0 Begin completing the square. Move the constant term to the right: Add '8' to each side of the equation. -8 + 3x + 8 + x2 = 0 + 8 Reorder the terms: -8 + 8 + 3x + x2 = 0 + 8 Combine like terms: -8 + 8 = 0 0 + 3x + x2 = 0 + 8 3x + x2 = 0 + 8 Combine like terms: 0 + 8 = 8 3x + x2 = 8 The x term is 3x. Take half its coefficient (1.5). Square it (2.25) and add it to both sides. Add '2.25' to each side of the equation. 3x + 2.25 + x2 = 8 + 2.25 Reorder the terms: 2.25 + 3x + x2 = 8 + 2.25 Combine like terms: 8 + 2.25 = 10.25 2.25 + 3x + x2 = 10.25 Factor a perfect square on the left side: (x + 1.5)(x + 1.5) = 10.25 Calculate the square root of the right side: 3.201562119 Break this problem into two subproblems by setting (x + 1.5) equal to 3.201562119 and -3.201562119.

Subproblem 1

x + 1.5 = 3.201562119 Simplifying x + 1.5 = 3.201562119 Reorder the terms: 1.5 + x = 3.201562119 Solving 1.5 + x = 3.201562119 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1.5' to each side of the equation. 1.5 + -1.5 + x = 3.201562119 + -1.5 Combine like terms: 1.5 + -1.5 = 0.0 0.0 + x = 3.201562119 + -1.5 x = 3.201562119 + -1.5 Combine like terms: 3.201562119 + -1.5 = 1.701562119 x = 1.701562119 Simplifying x = 1.701562119

Subproblem 2

x + 1.5 = -3.201562119 Simplifying x + 1.5 = -3.201562119 Reorder the terms: 1.5 + x = -3.201562119 Solving 1.5 + x = -3.201562119 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1.5' to each side of the equation. 1.5 + -1.5 + x = -3.201562119 + -1.5 Combine like terms: 1.5 + -1.5 = 0.0 0.0 + x = -3.201562119 + -1.5 x = -3.201562119 + -1.5 Combine like terms: -3.201562119 + -1.5 = -4.701562119 x = -4.701562119 Simplifying x = -4.701562119

Solution

The solution to the problem is based on the solutions from the subproblems. x = {1.701562119, -4.701562119}

Solution

x = {1.701562119, -4.701562119}

See similar equations:

| 27x=33 | | 100-50= | | 8cosx-3=0 | | F(-1)=3x^3-5x^2-2x-5 | | 5x-2=125 | | 3x-7i=3(3x-7u) | | 8n+32=4(7n-7) | | (3a^3)(5a^2)= | | 2h=-3g+52 | | 2-3ln(x+1)=8 | | 3-2*-4=w | | 4(x+6)=6(x-2)+3x-4 | | y=2x^2-12x-19 | | (2x-1)+2(2x+6)=4x-1 | | (2p+3)(2p-3)=(2p+10)(2p-10)-91p | | 3h+13h=20-2 | | 6x+7=3x+8 | | 2x+3(x-2)=4x-24+2x | | 6*-2=r-5r | | 7(x-9)-5=-68 | | 6*-2=r | | 15x=482 | | 3y-1+y+35=7+7y+33-5y | | 8w+6w=82 | | (x-4)2=(x-2) | | 4-t=2xa+21 | | 15x=498 | | x^2+27x-468=0 | | y^2-16y^2=0 | | 6x-5+8y=-22 | | -5*-3=15-7c | | x-9x=-4*6 |

Equations solver categories